Development of a Quality-of-Life Survey for Patients With Succinic Semialdehyde Dehydrogenase Deficiency, a Rare Disorder of GABA Metabolism. (November 2021) - Bose, Mousumi; Roullet, Jean-Baptiste; Gibson, K. Michael; Rizzo, William B.; Mansur, Hana M.; McConnell, Alice; Hoffman, Carolyn A.; DiBacco, Melissa L.; Pearl, Phillip L.
Succinic semialdehyde dehydrogenase deficiency (SSADHD), a rare disorder of GABA metabolism, presents with significant neurodevelopmental morbidity. Although there is a growing interest in the concept of quality of life through patient reports as a meaningful outcome in rare disease clinical trials, little is known about the overall impact of SSADHD from the patient/family perspective. The purpose of this study was to determine issues related to quality of life and patient/family experience through a focus group discussion with family caregivers of patients with SSADHD. The discussion included the input of 5 family caregivers, and highlighted concerns related to physical function, cognitive and intellectual function, psychological and behavioral function, social function, and family impact. These themes represent appropriate starting points in the development of a quality-of-life survey that may serve as a meaningful clinical tool in future studies of SSADHD.